Region of Birth and Child Mortality among Black Migrants to South Africa: Is there a foreign-born advantage? - Green, Tiffany L; Peters, Amos C (Migration Letters, 2016)
Much of the existing evidence for the healthy immigrant advantage comes from developed countries. We investigate whether an immigrant health advantage exists in South Africa, an important emerging economy. Using the 2001 South African Census, this study examines differences in child mortality between native-born South African and immigrant blacks. We find that accounting for region of origin is critical: immigrants from southern Africa are more likely to experience higher lifetime child mortality compared to the native-born population. Further, immigrants from outside of southern Africa are less likely than both groups to experience child deaths. Finally, in contrast to patterns observed in developed countries, we detect a strong relationship between schooling and child mortality among black immigrants.